Mechanics of the dicrotic notch: An acceleration hypothesis. (November 2020) - Gamrah, Mazen Abou; Xu, Jing; El Sawy, Amr; Aguib, Heba; Yacoub, Magdi; Parker, Kim H
The dicrotic notch is a prominent and distinctive feature of the pressure waveform in the central arteries. It is universally used to demarcate the end of systole and the beginning of diastole in these arteries. Despite its importance clinically, no physical mechanism for the formation of the dicrotic notch has been demonstrated convincingly. We first explore a mechanism based on the reflection of a backward wavefront from the aortic valve at the time of closure. This hypothesis is rejected on the basis of experimental evidence from measurements made in dogs. A new hypothesis is presented involving the acceleration of the aortic valve apparatus at the time of valve closure. This hypothesis is supported by new calculations of the acceleration of the aortic valve apparatus during the cardiac cycle based on computed tomography scans in man.